A case of recurrent and progressive respiratory failure. (August 2017) - Oblizajek, Nicholas R; Chen, Joy C Y; Tsang, Mazie; Chon, Tony Y
Abstract : Introduction: Patients presenting with dyspnea are common. Often times, patients carry previously anchored diagnoses, such as COPD, as a cause of their pulmonary symptoms. It is important, however, to perform a thorough history and physical examination in order to consider less common causes of dyspnea, such as in the case of this patient who was diagnosed with amyotrophic lateral sclerosis (ALS). The typical course for this disease process includes progressive limb and bulbar muscular weakness with eventual involvement of the respiratory musculature, ultimately leading to respiratory failure - the most frequent cause of death in ALS within 2 to 5 years of diagnosis. Case description: A 68-year-old woman presented to the hospital with recurrent episodes of dyspnea and carbon dioxide retention. She has a history of type II diabetes, hyperlipidemia, hypertension, cervical stenosis, and chronic obstructive pulmonary disease (COPD) requiring home oxygen therapy. Her medications included the following COPD regimen: short acting anticholinergic/beta agonist inhaler, mucolytic, steroid, long acting beta agonist nebulizers, and a Trilogy adaptive servo-ventilation device for nighttime breathing assistance. In the ED, workup showed pH 7.34, pCO2 95mmHg, and HCO3 of 50mmHg; chest x-ray was significant for mild hyperexpansion. On examination, she had mild proximal upper extremity weakness, bilateral thenar atrophy, and a nasal voice. She was in the ICU for 24-48 hours for intensive positive pressure therapy because of her severe carbon dioxide retention. Results and conclusions: Bedside pulmonary function testing was consistent with a restrictive process, and she was diagnosed with obesity hypoventilation. However, her BMI was only 39, and given her history of weakness and thenar atrophy, we were concerned for a neurologic process. Neurology found fibrillations with insertion and prominent fasciculations within the proximal right upper limb muscles on needle electromyography. Ultrasound examination with phrenic nerve stimulation showed reduced recruitment of large, complex motor unit potentials in both hemidiaphragms and intercostal muscles. With this constellation of symptoms, ALS was diagnosed. Other possible diagnoses were ruled out with neuroimaging, serologic, and cerebrospinal fluid studies. Take-home message: Progressive dyspnea as the major presenting symptom of ALS is exceedingly rare, occurring in less than 1% according to literature. It is important to keep ALS in the differential diagnosis in patients who present with progressive dyspnea and restrictive lung disease on pulmonary function testing because this diagnosis has significant prognostic difference compared to other entities such as obesity hypoventilation syndrome.